Spiritual elements in counseling process: counselors' perspective - Yusop, Yusni Mohamad; Mohd Saleh, Nur Diyanah; Wan Othman, Wan Norhayati; Zainudin, Zaida Nor (Human Resource Management Academic Research Society, 2023)
This study aims to identify the application of spiritual elements by counselors when conducting counseling sessions. The study sample consisted of 132 respondents who were counselors in one of the state under the Malaysian Ministry of Education (MoE). The study results show that the percentage of counselors who use spiritual elements is 84.4 while those who do not use spiritual elements in counseling sessions is 14.4. The study also found that spiritual elements are widely used in the intervention and action phase compared to building relationships, exploration, identifying problems, and termination. A total of 91.8 of those who responded agreed to use spiritual elements in counseling sessions compared to 8.3 who did not agree to use them. The study also found that 90.1 of respondents thought that spiritual elements should be present in counseling sessions compared to 9.8 who stated that there was no need to use spiritual elements in counseling sessions. The study suggests that future studies gather views from counselors across Malaysia and identify significant relationships between spiritual elements and related variables in determining the effectiveness of counseling for clients.